Use of the Stress-Relaxation and Dynamic Tests to Evaluate the Viscoelastic Properties of Dough from Soft Wheat Cultivars - Magaña-Barajas, Elisa; Ramírez-Wong, Benjamín; Torres-Chávez, Patricia I.; Morales-Rosas, I. (IntechOpen, 2012)
None